Innovation in civic education learning model to improve national defense skills in college students - Hanum, Fatikhah Fauziah; Murdiono, Mukhamad; Suyato, Suyato (Universitas Negeri Yogyakarta, 2024)
This research delves into the topic of national defense among college students and aims to uncover new and effective ways to integrate Civic Education to enhance students' national defense capabilities in the digital age. The study employs a mixed-method approach with a concurrent triangulation design. Through interviews with Civic educators, it became apparent that students lacked engagement with and enthusiasm for the subject matter. Quantitative data analysis revealed that while students exhibited a strong awareness of and patriotism for their country, they faced challenges in illustrating how their skills and competencies could be utilized to advance the nation. To address these issues, suggestions for innovative learning techniques included integrating a service-learning approach and incorporating online learning methods.